Intervensi Berbasis Kelompok Sebaya (Peer Group Suport) dalam Upaya Peningkatan Kepatuhan Pengobatan ARV pada ODHA - Iswanto Iswanto; Sri Yona; Etty Rekawati (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the effect of peer group support on adherence to ARV treatment. The method used is a systematic review by searching articles according to the formulation of research questions using the PICO formula through online database searches, namely Pubmed, PubMed, SAGE, Scopus, and Springer Link with full text), published 2020-2023. The results showed that peer group-based interventions were critical in increasing ARV adherence in PLHIV. In conclusion, peer group intervention for ODHAcan increase ARV adherence and thereby automatically improve the quality of life for ODHA. Keywords: HIV AIDS, Peer Group, Compliance